COLLECTED DOCUMENTS Bekiashev К.А., Bekiashev D.K., International Law. CoHected documents. Bipartite. Part I. - Moscow: TK Welby, Publishing House "Prospekt", 2006. - 1408 p. Bekiashev K.A., Bekiashev D.K., International Law. Collected documents. Bipartite. Part II. - Moscow: TK Welby, Publishing House "Prospekt", 2006. - 1456 p. - E. G. Moiseev (Московский журнал международного права, 2007)
The authors of the reviewed collection of international documents skillfully managed to choose the core documents of international law. These documents are assembled in two volumes, which include about 700 documents amounting to almost 2,900 pages. Documents are organized into 25 chapters. Each chapter consists of 4 groups of documents. The first group contains 242 universal documents, the second - 228 regional documents, the third group is compiled of 135 bilateral and other agreements concluded by the Russian Federation and foreign states, international organizations and other subjects of international law. Finally, the fourth group is formed by 89 national legal documents including constitutions, laws, and other normative acts of the Russian Federation and other states. The collection of documents has also very important background information with regard to each document's entry into force, the number of states - parties to it, the participation of the Russian Federation (with indication of the ratification date).The way of assembling the international documents is well thought-out. On the one hand, these are rare documents, and previously students had a difficulty finding them all in one book. On the other hand, these are the most important and necessary documents, which purposefully mould in students the specific way of thinking in terms of international law.The edition of 1,000 copies was sold out in a few days, which testifies to the collection's great value. Hopefully the "Prospect" Publishing House will make sure that the supply will meet the demand for the collected documents under review.